Analysis of Cyber Harassment Violence Management Using the 5R Method on Female Students at Unimuda Sorong Southwest - Agfajrina Cindra Pamungkas; Muhamad Hasan Rumlus; Nadila (Yayasan Ilomata, 2026)
The phenomenon of cyber harassment as part of Online Gender-Based Violence (KBGO) is increasing and has a significant impact on female students, especially in areas with uneven digital literacy such as Southwest Papua. This study aims to analyze the change in students' abilities after the intervention of the 5R Method (Recognize, Respond, Record, Report, Refer) in dealing with cyber harassment, with the novelty in the form of the application of the 5R method as a gender-based structured intervention model that is empirically measured in the context of local universities. The study used a mixed methods method with a one group pretest– posttest design combined with a phenomenological approach, involving 60–70 female students of UNIMUDA Sorong who were selected by purposive sampling. The intervention was carried out through training for 3 sessions in 2 weeks, using a Likert scale questionnaire instrument (1–5) covering five 5R domains with a reliability of Cronbach's Alpha 0.82. The results showed an increase in the mean score from 2.71 to 3.89 (Δ=1.18), with the paired sample t-test showing a significant difference (p<0.05) and a measure of Cohen's effect d of 0.85 (large category). The qualitative findings reinforced these results, showing an increase in awareness, the ability to document digital evidence, and the use of reporting channels and psychosocial support, accompanied by an increased sense of post-intervention security. Although the limitations of the design without a control group limit causality claims, these findings suggest that the 5R method has the potential to be a relevant approach in supporting cyber harassment countermeasures and strengthening gender-based digital literacy in the college environment.